2014
DOI: 10.1089/jir.2013.0085
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ and TNF-α Are Involved During Alzheimer Disease Progression and Correlate with Nitric Oxide Production: A Study in Algerian Patients

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease leading to a progressive and irreversible loss of mental functions. It is characterized by 3 stages according to the evolution and the severity of the symptoms. This disease is associated with an immune disorder, which appears with significant rise in the inflammatory cytokines and increased production of free radicals such as nitric oxide (NO). Our study aims to investigate interferon (IFN)-γ and tumor necrosis factor-α (TNF-α) involvement in NO producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 34 publications
3
61
0
Order By: Relevance
“…Studies have indicated that NO can generate a high level of pro-inflammatory cytokines to strengthen neurotoxicity, and this increase is consequently related to the development of AD. 26 Ab blocks the normally reparative effects of up-regulated vascular endothelial growth factor and nitric oxide synthases (NOS) and may accelerate in vivo vascular pathophysiology in AD. 27 Excessive NO generated by NOS could strengthen the neurotoxicity because of the inhibition of glutamate reuptake, hence contributing to neuronal death and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that NO can generate a high level of pro-inflammatory cytokines to strengthen neurotoxicity, and this increase is consequently related to the development of AD. 26 Ab blocks the normally reparative effects of up-regulated vascular endothelial growth factor and nitric oxide synthases (NOS) and may accelerate in vivo vascular pathophysiology in AD. 27 Excessive NO generated by NOS could strengthen the neurotoxicity because of the inhibition of glutamate reuptake, hence contributing to neuronal death and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this suggests that NO production is IFN-γ-dependent in AD. 37 On the other hand, IFN-γ is a known inhibitor of APP fragment production. IFN-γ can prevent amyloid deposition during inflammatory processes in both non-neuronal and neuronal tissues.…”
Section: Interleukin-18 and Interferon-γmentioning
confidence: 99%
“…5 Importantly, Belkhelfa et al revealed recently that a high level of NO is associated with the rise of TNF-α levels in patients in the severe stages of AD. 37 In response to numerous intrinsic and extrinsic stimuli, TNF-α is produced by microglia, astrocytes and neurons in the brain. In addition, genetic and epidemiological findings have implicated augmented levels of TNF-α in the brain as a risk factor for AD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reason why changes of AA in the CNS link with that of SAA is considered to be the following: SAA inhibits muscarinic ACh activity of parasympathetic neurons and produces cytokine activation with macrophages; then, the proinflammatory cytokines penetrate into the brain and possibly activate the microglia. The activated microglia in the brain produces proinflammatory cytokines accelerating AD [16,18,19]. Therefore, any AA produced in the brain or peripheral tissue causes inflammation activating microglia or macrophages, respectively; the produced proinflammatory cytokines penetrate the BBB both ways, and then the AA reflects each region.…”
Section: Does Saa Reflect Aa In the Brain?mentioning
confidence: 99%